2004
DOI: 10.1007/s00406-004-0544-8
|View full text |Cite
|
Sign up to set email alerts
|

Long?term course and outcome of obsessive?compulsive patients after cognitive?behavioral therapy in combination with either fluvoxamine or placebo

Abstract: Longitudinal studies with very long follow-up periods of patients with obsessive-compulsive disorder (OCD) who have received adequate treatment are rare. In the current study, 30 of 37 inpatients (81%) with severe OCD were followed up 6-8 years after treatment with cognitive-behavioral therapy (CBT) in combination with either fluvoxamine or placebo in a randomized design. The significant improvements (with large effectsizes) in obsessive-compulsive symptoms from pre- to post-treatment (41% reduction on the Y-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 42 publications
6
41
0
14
Order By: Relevance
“…Additionally, Rufer et al in a 7-year follow-up after CBT in combination with either fluvoxamine or placebo, reported the maintenance of the results in 45% of the patients in the period. 17 In our study, an increase was observed in the number of patients who met full remission criteria during the follow-up period, from 9 patients (21.4%) immediately after treatment, to 13 (31.0%) in the 24 th month, an increase of 44.4%. The full remission rates were similar to those found in related studies, 5,17 but a little higher than those reported in others.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, Rufer et al in a 7-year follow-up after CBT in combination with either fluvoxamine or placebo, reported the maintenance of the results in 45% of the patients in the period. 17 In our study, an increase was observed in the number of patients who met full remission criteria during the follow-up period, from 9 patients (21.4%) immediately after treatment, to 13 (31.0%) in the 24 th month, an increase of 44.4%. The full remission rates were similar to those found in related studies, 5,17 but a little higher than those reported in others.…”
Section: Discussionsupporting
confidence: 50%
“…It seems probable that some Imams may unintentionally provide suggestions that increase and aggravate the OCD symptoms of religious help seekers, which is consistent with the findings of Deacon, Vincent, and Zhang (Deacon et al 2013) among Christian clergy members. If these findings generalise beyond the sample examined here, then this would provide an important direction for targeting early intervention for Muslim women with OCD-W symptomatology, as shorter delays between emergence of symptoms and commencing treatment have been associated with better outcomes (Rufer et al 2005). More research examining the experience of Imams in regard to their understanding of OCD and also the nature of the advice provided to Muslim help-seekers regarding their religious OCD symptoms would be beneficial and could inform the development of strategies to overcome large delays in seeking appropriate treatment.…”
Section: Discussionmentioning
confidence: 82%
“…This might indicate that OCD patients usually require ongoing treatment to maintain their improvements over long periods (Rufer et al 2005).…”
Section: Other Medicationsmentioning
confidence: 99%